The Effect of Eggs on Growth Among Infants 6–12 months of Age in Rural Bangladesh: A Cluster Randomized Controlled Trial. (29th May 2020) - Pasqualino, Monica; Shaikh, Saijuddin; Hossain, Md Iqbal; Islam, Md Tanvir; Ali, Hasmot; Haque, Rezwanul; Ayesha, Kaniz; Wu, Lee; Schuh, Holly; Dyer, Brian; Hasan, Khaled; Alland, Kelsey; et al.
Abstract: Objectives: To assess the impact of daily egg supplementation on infant growth from 6–12 months of age in Bangladesh. Methods: A cluster randomized controlled trial was conducted in rural Bangladesh to test the effect of daily egg supplementation and nutrition education versus nutrition education alone on linear growth and stunting prevalence among infants. Infants were enrolled at 3 months of age and assigned to a trial arm based on their geographic sector of residence. Households were visited weekly to distribute eggs and monitor compliance starting at 6 months of age. Length, weight, head circumference, and mid upper arm circumference were measured at 6, 9, and 12 months, as well as dietary intake from home foods in the last 24 hours. Analyses were conducted on an intention-to-treat basis. Linear regression models were developed for continuous outcomes. For dichotomous outcomes, prevalence ratios were estimated using log-binomial regression models. Generalized estimating equations were used with all models to account for clustering. Each model was adjusted for the baseline measure of the outcome variable. Results: Overall, 909 infants were enrolled in the treatment arm from 142 clusters and 842 infants in the control arm from 140 clusters. Prevalence of stunting at baseline was 19.4%, wasting was 6.7%, and underweight was 18.1%. After 6 months of supplementation, the intervention had no effect on mean length-for-age z-scores (β = 0.05, 95% CI: −0.12, 0.23) or prevalence of stunting (PR = 1.00, 95% CI: 0.90, 1.10). Infants in the egg arm had significantly higher mean weight-for-length z-scores (β = 0.11, 95% CI: 0.04, 0.18) and weight-for-age z-scores (β = 0.08, 95% CI: 0.03, 0.12), adjusting for baseline measures of the outcomes. Our presented results will include findings from mixed-effects regression analyses assessing the effect of the intervention on growth rate. Conclusions: The provision of a daily egg for 6 months to infants in rural Bangladesh had an effect on ponderal but not linear growth. Funding Sources: Bill and Melinda Gates Foundation.